On a generalization of an approximation operator defined by A. Guessab. Issue 12 (10th September 2021) - Taghavi, Ali; Azimi Roushan, Tahere
Abstract : We approximate a class of operator convex functions via some numerical results which were obtained by Guessab, and determine the error of the approximation. Finally we represent a characterization of special operator integration, by which we obtain error bound for left-hand side inequality of Hermite-Hadamard inequality.